Assessing Social Capital for Organisational Performance: Initial Exploratory Insights From Ghana - Ofori, Dan; Sackey, Jocelyn (Organizations and Markets in Emerging Economies, 2010)
Social Capital is a concept that describes good quality social relations that can lead to mutual benefit. The fundamental proposition of social capital theory is that networks of relationships grant access to resources, especially information benefits not available to non-members of the network. This study assessed the functions of social capital within Ghanaian organizations, described the patterns and determinants of social capital use within organizations and explored how social capital contributes to firm performance using a sample frame of firms listed in the Ghana Club 100. A questionnaire field survey supplemented by personal interviews was chosen as the most appropriate design for this investigation. Employees were sampled across the organizational hierarchy based on their responsibilities held, positions, type of relationship held with others within the organisation. Data was also collected on the demographic characteristics and organisational dynamics. The results showed that social capital is critical to knowledge sharing in the Ghanaian organization; that it helps to get things done and helps in the attainment of organisational objectives. The findings also suggested that three determinate variables of social capital: reciprocity, trust and institutional ties, have the most significant positive relationship with organisational performance. In view of that, the study recommends that firms take a proactive approach towards promoting, building and maintaining viable social networks within their structures in order to derive maximum benefit from it.
Keywords: social capital; organisational performance; Ghana